Semantics of Home / House Image in A.J. Cronin’s Novel “Three Loves” - Anna A. Novikova (RUDN Journal of Language Studies, Semiotics and Semantics)
The relevance of this study analyzing the semantics of the image of the house in the plot development of the novel is determined by the interest of modern literary studies to the comprehension of the artistic reality of the work, as well as to the peculiarities of the writer’s individual style and the potentialities of language realized in the semantics of the artistic image. The study used a complex methodology represented by a set of methods and research techniques of descriptive nature. The linguistic mechanisms which create the semantics of linguistic images and the typology of linguistic, textual and cultural images are studied by the methods of semantic analysis, cognitive linguistics (frame semantics, mental space), psychology (apperception and comparison of objects as a prerequisite for metaphorization). The author considers that the image of home/house in the novel becomes a metaphor of existence and, at the same time, a place to llive in. This ambivalent meaning is explained by the peculiarity of the artistic thinking of the realist writer, in whose work the key place is occupied by the motive of searching for truths and self. At the same time, the description of the house (factual and expressive information of the image) gives the reader opportunity of gaining insight into the characters’ inner world, contributing to a deeper understanding of the hero’s psychology and uncovering his hidden experiences, thoughts, desires, and mental impulses, which were created by the author, and develop ways to implement the image system and preserves the author’s intention, so deciphering the ‘code’ of the semantics of the image of the home/house in the above-mentioned novel outlines new ways to study the features of the writer’s fiction prose.